Brazing paste composition and brazing method using same
The brazing paste composition with spherical copper powder of specific particle size and low oxygen content addresses the challenges of poor wetting and oxidation in stainless steel brazing, achieving defect-free and aesthetically pleasing results in an inert gas atmosphere.
Patent Information
- Application Number
- JP2021067452
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2021-04-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-04-13
AI Technical Summary
Brazing stainless steel using traditional copper braze pastes often results in poor wetting, interrupted fillets, and oxidation, leading to defects and a compromised appearance, especially when performed in an inert gas atmosphere for safety reasons.
A brazing paste composition featuring spherical copper powder with a specific particle size distribution (5-40% passing through a 45 μm sieve) and low oxygen content (≤0.02% by mass) is used, along with an organic binder and solvent, to prevent chromium oxidation and ensure good fillet formation in an inert gas atmosphere.
The brazing paste composition effectively prevents chromium oxidation, ensures excellent fillet formation without defects, and maintains the appearance of stainless steel, even when brazed in an inert gas atmosphere.
Smart Images

Figure 0007654451000002 
Figure 0007654451000003 
Figure 0007654451000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a brazing paste composition and a brazing method using the same, and more particularly to a brazing paste composition suitable for brazing stainless steel, which contains as a main component spherical copper powder having a specific particle size distribution and a low oxygen content at a specific particle size, and a brazing method using the same. [Background technology]
[0002] Brazing has been known as a method for joining metals, ceramics, etc. Brazing is a type of welding method in which a brazing material is used that has a melting point lower than that of the objects to be brazed and is 450°C or higher. More specifically, the brazing material is applied to the surface of one base material and heated to a temperature at which the brazing material melts but not the base material, causing the thin film of brazing material to diffuse to the joining surface with the other base material by capillary action and solidify, thereby joining the base materials together.
[0003] Generally, brazing of stainless steel materials uses brazing materials mainly composed of nickel, copper, etc. Copper brazing materials are mainly used in the form of wire, ring, or foil, and paste brazing materials made by mixing copper powder with organic binders, etc., have been developed in consideration of the work site and work environment, as described in, for example, JP 2003-275895 A (Patent Document 1). Brazing using copper brazing materials is performed at a high temperature of about 1100°C, and oxidation must be prevented, so it is mainly performed in a vacuum furnace or a hydrogen furnace.
[0004] However, when attempting to braze stainless steel using a paste-like copper brazing filler as described in Patent Document 1, the chromium contained in the stainless steel is oxidized, resulting in poor wetting of the brazing filler metal on the stainless steel surface, causing problems such as the brazed portion (fillet) being broken after brazing or the brazing filler metal being repelled and remaining as balls or grains. There is also the problem that the oxidation of chromium causes the stainless steel surface to discolor and lose its luster, deteriorating its appearance.
[0005] On the other hand, in order to prevent the oxidation of chromium contained in stainless steel, it is considered effective to perform brazing in a reducing gas atmosphere containing hydrogen. However, since reducing gases such as hydrogen are flammable and may cause explosions, there has been a need for the development of a brazing material that can prevent the oxidation of chromium in stainless steel even in an inert gas atmosphere from the standpoint of safety, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2003-275895 A Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a paste-like composition for brazing that is particularly suitable for brazing stainless steel, and that is capable of achieving good fillet formation (appearance) in the brazed portion after brazing without causing brazing defects such as breakage of the fillet or generation of residue even when brazing in an inert gas atmosphere, and a brazing method in an inert gas atmosphere using the same. [Means for solving the problem]
[0008] In order to solve the above problems, the inventors focused on preventing the oxidation of chromium in stainless steel, and conducted extensive research into the copper powder used in a brazing paste composition, particularly into its shape, particle size, properties, etc., and discovered that the above problems can be solved by using copper powder that has a specific particle size distribution and a low oxygen content at a specific particle size, thereby completing the present invention.
[0009] That is, according to the present invention, there is provided a brazing paste composition comprising spherical copper powder, the mass ratio of particles passing through a sieve with a mesh size of 45 μm being 5 mass% or more and 40 mass% or less, and the oxygen content of particles constituting the copper powder that pass through a sieve with a mesh size of 45 μm and remain on a sieve with a mesh size of 20 μm being 0.02 mass% or less, and a brazing method using the same is provided.
[0010] As a result, the brazing paste composition of the present invention is particularly suitable for brazing stainless steel, and even when brazing in an inert gas atmosphere, it is possible to obtain good fillet formation (appearance) in the brazed part after brazing without causing brazing defects such as breaks in the fillet or the generation of residue.
[0011] The brazing paste composition of the present invention contains copper powder and an organic solvent for wetting the copper powder. The brazing paste composition of the present invention may also contain other organic binders, dispersants, etc. depending on the application.
[0012] <Copper powder> The copper powder used in the brazing paste composition of the present invention is preferably spherical, and the particle size distribution is preferably such that the mass ratio of particles passing through a 45 μm sieve to all particles constituting the copper powder is 5% by mass to 40% by mass, more preferably 5% by mass to 30% by mass. It is not practical to set the mass ratio of copper powder passing through a 45 μm sieve to less than 5% by mass in terms of production costs, while if the mass ratio of copper powder passing through a 45 μm sieve exceeds 40% by mass, the viscosity of the resulting paste composition increases and the applicability becomes poor.
[0013] In addition, the oxygen content of the copper powder used in the present invention is preferably such that the oxygen content of particles that pass through a sieve with 45 μm openings and remain on a sieve with 20 μm openings is 0.02 mass% or less among all particles constituting the copper powder.
[0014] If the oxygen content of the copper powder within the above particle size range exceeds 0.02% by mass, the oxygen contained in the copper powder oxidizes the chromium in the base stainless steel, and the wettability of the brazing material is deteriorated due to the formation of an excessive oxide film, which causes the fillet to break or the brazing material to be easily repelled and remain as balls or grains. In addition, the oxidation of chromium may cause the stainless steel surface to discolor or lose its luster, resulting in a poor appearance. There is no particular lower limit for the oxygen content of the copper powder, and ideally it is preferably 0% by mass. However, from the viewpoint of production costs, etc., if the oxygen content is 0.01% by mass or more, it can be used suitably without causing the above-mentioned brazing defects.
[0015] The volume average particle diameter (D 50 The volume average particle diameter (D 50 ) is within the above range, good coatability can be obtained without causing brazing defects such as breaks in the fillet or poor appearance.
[0016] The specific surface area of the spherical copper powder used in the present invention, as measured by the BET method, is 0.005 m 2 / g or more 0.06m 2 If the specific surface area of the spherical copper powder measured by the BET method is within the above range, the copper powder in the paste will not separate during storage, and good coatability can be obtained.
[0017] In addition, from the viewpoint of obtaining good fluidity of the brazing material and good wettability with the base material, it is preferable to use spherical copper powder having a purity of 99% by mass or more, and more preferably 99.78% by mass or more and 99.95% by mass or less.
[0018] In addition, the spherical copper powder used in the present invention contains the following components other than copper: By massIt is preferable that the brazing material contains 500 ppm to 2000 ppm of phosphorus, and more preferably 1000 ppm to 1500 ppm of phosphorus. If the brazing material contains 500 ppm to 2000 ppm of phosphorus, the brazing material will have a less residue-like appearance after brazing. If the phosphorus content exceeds 2000 ppm, the fluidity of the brazing material will be poor, and problems such as brazing material cutting may occur.
[0019] <Organic binder> The brazing paste composition of the present invention may contain an organic binder as necessary. As the organic binder, any known binder can be used without any particular limitation as long as it can be used for brazing materials. Among organic binders, butyl rubber in particular is suitably used since it is easily pyrolyzed without falling off during the process up to brazing and does not cause brazing defects due to residual carbon, etc.
[0020] Butyl rubber is a copolymer of isobutylene and isoprene monomers, and has a structure that is easily decomposed by heating because the bonds between the isobutylene and isoprene monomers are linear. Therefore, butyl rubber is easily decomposed by heating during the brazing process without being affected by the atmosphere in the brazing furnace.
[0021] <Organic solvent> The organic solvent used in the brazing paste composition of the present invention is not particularly limited as long as the binder is soluble in the organic solvent, and toluene, hexane, octane, cyclohexane, etc. can be used alone or in a mixture of two or more kinds, and it is preferable to use a hydrocarbon solvent that does not contain oxygen. The content of the organic solvent may be appropriately added to adjust the viscosity, etc. of the paste composition.
[0022] <Brazing method> The brazing paste composition of the present invention can be used by applying it to a part or the whole of the surface of the base material to be brazed. As the application method, a known method can be adopted, such as a dispenser, screen printing, brush application, spray application, etc.
[0023] Although the paste composition of the present invention can be brazed by heating it as it is after application, it is preferable to dry it once to volatilize the organic solvent. The paste composition may be dried at room temperature or at a temperature of about 30°C to 200°C as necessary. If the paste composition is not dried, the organic solvent in the applied paste composition will rapidly vaporize, and the vaporized gas may cause the applied paste composition to scatter.
[0024] In the present invention, after drying the paste composition, brazing can be performed under an inert gas atmosphere at normal pressure using a brazing furnace such as a muffle furnace. The inert gas is not particularly limited, and inert gases such as argon gas and / or helium gas can be used, but argon gas is preferably used. As the brazing furnace, a carbon muffle furnace is preferably used because it absorbs a small amount of oxygen remaining in the inert gas.
[0025] The brazing temperature of the paste-like composition of the present invention is preferably 1100° C. or higher and 1150° C. or lower, and more preferably 1120° C. or higher and 1140° C. or lower. When the brazing temperature is 1120° C. or higher, the brazing time is preferably maintained for 5 minutes or longer and 30 minutes or shorter. Note that the brazing temperature generally means the temperature of the base material used for brazing, but when brazing is performed in a brazing furnace such as a muffle furnace, the atmospheric temperature of the brazing furnace shows approximately the same history as the temperature of the base material, and therefore the atmospheric temperature of the brazing furnace may be used instead.
[0026] When brazing is performed under the above-mentioned conditions, the paste composition of the present invention suppresses coloration of the base material and also provides a good melting state of the brazing material made of copper powder or the like. Effect of the Invention
[0027] According to the present invention, there is provided a paste-like composition for brazing, which contains spherical copper powder, the mass ratio of particles of the copper powder passing through a sieve with a mesh size of 45 μm being 5 mass% or more and 40 mass% or less, and the oxygen content of particles constituting the copper powder that pass through a sieve with a mesh size of 45 μm and remain on a sieve with a mesh size of 20 μm is 0.02 mass% or less.
[0028] As a result, the brazing paste composition of the present invention and the brazing method using the same are particularly suitable for brazing stainless steel, and have the excellent effect of being able to obtain good fillet formation (appearance) in the brazed part after brazing, without causing brazing defects such as breaks in the fillet or the generation of residue, even when brazing in an inert gas atmosphere. [Brief description of the drawings]
[0029] [Figure 1] 1A is a schematic plan view of a test sample for evaluating the molten state of the brazing fillet, the formation state of the fillet, and the residue, and FIG. 1B is a central cross-sectional view of the same. [Diagram 2] 1A is a plan view showing a schematic overview of a test sample for evaluating the coloring state of a base material when brazed, and FIG. 1B is a central cross-sectional view thereof. [Diagram 3] 1A is a plan photograph showing the molten state of the brazing filler metal of the test sample of Example 1, and FIG. 1B is a perspective photograph taken from an oblique direction. [Figure 4] 1A is a plan photograph showing the molten state of the brazing filler metal of the test sample of Example 2, and FIG. 1B is a perspective photograph taken from an oblique direction. [Diagram 5] 1A is a plan photograph showing the molten state of the brazing filler metal of the test sample of Comparative Example 1, and FIG. 1B is a perspective photograph taken from an oblique direction. [Figure 6] 1A is a plan photograph showing the molten state of the brazing filler metal of the test sample of Comparative Example 2, and FIG. 1B is a perspective photograph taken from an oblique direction. [Figure 7]1A is a plan photograph showing the molten state of the brazing material of the test sample of Comparative Example 3, and FIG. 1B is a perspective photograph seen from an oblique direction. [Figure 8] 1A is a plan photograph showing the molten state of the brazing material of the test sample of Comparative Example 4, and FIG. 1B is a perspective photograph taken from an oblique direction. [Figure 9] 1A is a plan photograph showing the molten state of the brazing material of the test sample of Comparative Example 5, and FIG. 1B is a perspective photograph seen from an oblique direction. [Figure 10] 1 is a photograph of the back surface of a lid material showing the colored state of the base material of the test sample of Example 1. [Figure 11] 1 is a photograph of the back surface of a lid material showing the colored state of the base material of a test sample of Example 2. [Figure 12] 1 is a photograph of the back surface of a lid material showing the colored state of the base material of a test sample of Comparative Example 1. [Figure 13] 1 is a photograph of the back surface of a lid material showing the colored state of the base material of a test sample of Comparative Example 2. [Figure 14] 13 is a photograph of the back surface of a lid material showing the colored state of the base material of the test sample of Comparative Example 3. [Figure 15] 13 is a photograph of the back surface of a lid material showing the colored state of the base material of the test sample of Comparative Example 4. [Figure 16] 13 is a photograph of the back surface of a lid material showing the colored state of the base material of the test sample of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Hereinafter, a brazing paste composition according to one embodiment of the present invention and a brazing method using the same will be described in detail with reference to the drawings. Note that the present invention is not limited to the examples shown below, and various modifications are possible within the scope of the technical concept of the present invention. EXAMPLES
[0031] <1. Preparation of brazing paste> The brazing paste composition according to one embodiment of the present invention and the brazing paste composition of the comparative example were produced using the following raw materials and conditions (see "Table 1"). [Example 1] Copper powder with a purity of 99% by mass or more produced by atomization method. By mass Phosphorus content less than 1 ppm, volume average particle size (D 50 85 g of commercially available spherical copper powder a having a diameter of 74 μm was used, and 3 g of Exxon Butyl 268 (manufactured by Exxon Chemical Co., Ltd.) as an organic binder and 0.5 g of Disparlon 308 (manufactured by Kusumoto Chemical Co., Ltd.) as a thickener were dissolved in 13.5 g of toluene as an organic solvent and added to this copper powder, and then mixed with a stirrer to prepare the brazing paste composition of Example 1.
[0032] [Example 2] The copper powder is manufactured by atomization and has a purity of 99% by mass or more, a phosphorus content of 0.12% by mass, and a volume average particle diameter (D 50 A brazing paste composition of Example 2 was prepared under the same conditions as in Example 1, except that 85 g of commercially available spherical copper powder b of 66 μm was used.
[0033] [Comparative Example 1] The copper powder is manufactured by atomization and has a purity of 99% by mass or more, a phosphorus content of 0.11% by mass, and a volume average particle diameter (D 50 A brazing paste composition of Comparative Example 1 was prepared under the same conditions as in Example 1, except that 85 g of commercially available spherical copper powder c of 36 μm was used.
[0034] [Comparative Example 2] The copper powder is manufactured by atomization and has a purity of 99% by mass or more, a phosphorus content of 0.12% by mass, and a volume average particle diameter (D 50 A brazing paste composition of Comparative Example 2 was prepared under the same conditions as in Example 1, except that 85 g of commercially available spherical copper powder d of 54 μm was used.
[0035] [Comparative Example 3] The copper powder is manufactured by atomization, has a purity of 99% by mass or more, and has a volume average particle diameter (D 50A brazing paste composition of Comparative Example 3 was prepared under the same conditions as in Example 1, except that 85 g of commercially available non-spherical copper powder e having a diameter of 34 μm was used.
[0036] [Comparative Example 4] The copper powder is manufactured by atomization, has a purity of 99% by mass or more, and has a volume average particle diameter (D 50 A brazing paste composition of Comparative Example 4 was prepared under the same conditions as in Example 1, except that 85 g of commercially available non-spherical copper powder f of 30 μm was used.
[0037] [Comparative Example 5] The copper powder is manufactured by atomization and has a purity of 99% by mass or more, a phosphorus content of 0.03% by mass, and a volume average particle diameter (D 50 A brazing paste composition of Comparative Example 5 was prepared under the same conditions as in Example 1, except that 85 g of commercially available spherical copper powder of 40 μm was used.
[0038] 2. Evaluation of brazing paste <Measurement of copper powder characteristics> (1) Volume average particle size Volume average particle size of copper powder (D 50 ) indicates the particle diameter (μm) at 50% of the volume average particle diameter in the volume cumulative particle size distribution curve. The volume average particle diameter was measured using a laser diffraction / scattering type particle size distribution measuring device (instrument name: Microtrac, manufactured by Microtrac-Bell). For example, the volume average particle diameter (D 50 ) means the particle size (μm) at 50% cumulative density in a volume cumulative particle size distribution curve in which the vertical axis is cumulative frequency (%) and the horizontal axis is particle size (μm).
[0039] (2) Specific surface area by BET method The specific surface area of the copper powder measured by the BET method was measured using a specific surface area device (device name: "Macsorb model-1210", manufactured by Mountec Co., Ltd.).
[0040] (3) Measurement of particle size distribution The mass fraction of copper powder particles passing through a sieve with 45 μm openings (V -45) was calculated from the mass B of the copper powder that passed through a JIS standard sieve made of stainless steel alloy with a mesh size of 45 μm and the mass A of the copper powder before passing through the sieve, according to the following formula. V -45 (mass%)=(B / A)×100
[0041] (4) Measurement of oxygen content The oxygen content of the copper powder was measured by collecting the copper powder that passed through a stainless steel alloy JIS standard sieve mesh with 45 μm openings and remained on a stainless steel alloy JIS standard sieve with 20 μm openings, and using an inert gas fusion-non-dispersive infrared absorption method (measuring device name: EMGA-920, manufactured by Horiba, Ltd.).
[0042] <Brazing evaluation> (1) Preparation of brazed samples A stainless steel plate (SUS304, 50 × 50 × 3 mm) substrate and a stainless steel pipe (SUS304, φ34 × 17t) were assembled as shown in FIG. 1, and 4 g of the brazing paste composition of Examples 1 and 2 and Comparative Examples 1 to 5 was applied to the inside of the stainless steel pipe, followed by natural drying at room temperature for 18 hours to prepare a test sample. The naturally dried test sample was transferred into a carbon muffle furnace (Oxynon furnace, manufactured by Kanto Yakin Kogyo Co., Ltd.) and brazed at a brazing temperature of 1120° C. for 15 minutes in an argon atmosphere at normal pressure.
[0043] (2) Brazing evaluation After brazing was completed, the brazed portion between the stainless steel plate and the stainless steel pipe was visually inspected for the melted state of the brazing material, the state of fillet formation (appearance) and the presence or absence of residue, and evaluated according to the following criteria.
[0044] (Melted state of brazing material) "A"...Good "B": The flow of the brazing material is a little poor. "C" The brazing filler metal is not melted or does not wet with the base metal.
[0045] (Fillet formation state) "A": A continuous fillet is formed "B" - The fillet is interrupted "C": Fillet is not formed or is extremely small
[0046] (residue) "A" - No residue "B": A small amount of black residue is visible. "C": Granular residue is visible.
[0047] <Evaluation of base material coloring> (1) Preparation of a sample to confirm the base material color A stainless steel plate (SUS304, 50×50×3 mm) substrate and a stainless steel pipe (SUS304, φ34×17t) were assembled as shown in Fig. 2, and 4 g of the brazing paste composition of Examples 1 and 2 and Comparative Examples 1 to 5 was applied to the inside of the stainless steel pipe and naturally dried at room temperature for 18 hours. Furthermore, a test sample for confirming the coloring of the base material was prepared by covering the upper part of the stainless steel pipe with a cover material of the same stainless steel plate (SUS304, 50×50×3 mm) as the lower substrate. The above test sample was transferred into a carbon muffle furnace (Oxynon furnace, manufactured by Kanto Yakin Kogyo Co., Ltd.) and brazed at a brazing temperature of 1120°C for 15 minutes under an argon atmosphere at normal pressure.
[0048] (2) Evaluation of base material coloration After the brazing was completed, the appearance of the back surface (inner surface) of the stainless steel plate lid was visually observed and evaluated according to the following criteria.
[0049] (base material coloring) "A": The base material (covering material) is not colored and is in a shiny state. "B": The base material is cloudy "C": There is a lot of discoloration on the base material, making it worthless.
[0050] Table 1 shows the amounts of each component mixed into the brazing paste compositions of Examples 1 and 2 and Comparative Examples 1 to 5, the characteristics of the copper powder used, and the evaluation of brazing using the brazing paste compositions of Examples 1 and 2 and Comparative Examples 1 to 5. [Table 1]
[0051] <Consideration> 3, 4 and 5 to 9 show plan photographs (a) and oblique photographs (b) of the test samples of Examples 1 and 2 and Comparative Examples 1 to 5, respectively, showing the molten state of the brazing material. Also, Figs. 10, 11 and 12 to 16 show rear surface photographs of the lids, showing the colored state of the base material of the test samples of Examples 1 and 2 and Comparative Examples 1 to 5.
[0052] Comparing the brazing paste compositions of Examples 1 and 2 with the brazing paste compositions of Comparative Examples 1 to 5 from Table 1 and FIGS. 3 to 16, it was found that the brazing paste compositions of Examples 1 and 2 provided excellent brazing, particularly in brazing stainless steel under an inert gas atmosphere, with a good molten state of the brazing material, without breaks in the fillet or generation of residue, and without discoloration or coloring of the base material (no brazing defects).
[0053] In addition, when Examples 1 and 2 are compared with Comparative Examples 1 to 5, or Comparative Examples 1 and 2 are compared with Comparative Examples 3 to 5, it was found that the lower the oxygen content of the copper powder that passes through a sieve with a mesh size of 45 μm and remains on a sieve with a mesh size of 20 μm among all the copper powders constituting the brazing paste composition, the better the melting state of the brazing material and the like, and the more excellent the brazing tends to be obtained. In particular, in the case of Examples 1 and 2, it was found that extremely excellent brazing can be obtained when the oxygen content of the copper powder in the brazing paste composition is suppressed to 0.02 mass% or less. This is presumably due to the fact that the oxygen content of the copper powder of a specific particle size is reduced, thereby suppressing the formation of an excessive oxide film on the base material.
[0054] When comparing Example 1 and Example 2 with each other, or Comparative Examples 1 and 2 with Comparative Examples 3 to 5 with each other, the components other than copper constituting the brazing paste composition are: By mass It has been found that a brazing material containing 500 ppm to 2000 ppm of phosphorus results in a post-brazing appearance with less residue. However, if the phosphorus content exceeds 2000 ppm, the fluidity of the brazing material decreases, which may cause problems such as brazing material breaking.
[0055] By comparing the brazing paste compositions of Examples 1 and 2 with Comparative Examples 1 to 5, it was found that when the mass proportion of copper powder passing through a sieve with 45 μm openings among all the copper powder constituting the brazing paste composition is preferably 5 mass % or more and 40 mass % or less, more preferably 5 mass % or more and 30 mass % or less, an appropriate viscosity is obtained and the applicability is improved.
[0056] In addition, the brazing paste compositions of Examples 1 and 2 have a smaller volume average particle diameter (D 50 It was found that when the fillet width is relatively large, ie, 30 μm or more and 90 μm or less, brazing defects such as discontinuity of the fillet and poor appearance do not occur, and good coatability can be obtained.
[0057] Furthermore, in the brazing paste compositions of Examples 1 and 2, the specific surface area of the copper powder constituting the brazing paste composition by the BET method is 0.005 m compared with Comparative Examples 1 to 5. 2 / g or more 0.06m 2 It was found that when the copper powder content is 1 / g or less, separation of the copper powder in the paste is suppressed and good coatability can be obtained. [Explanation of symbols]
[0058] 1. Paste composition for brazing 2. Base material (stainless steel plate) 3. Stainless steel pipe 4. Cover material (stainless steel plate) 5. Fillet 6 Residues (colored brazing filler metal, grains and balls) 7. Coloring evaluation section
Claims
1. A composition comprising copper powder, The mass ratio of particles passing through a sieve having an opening of 45 μm in the copper powder is 5 mass% or more and 40 mass% or less, The oxygen content of particles constituting the copper powder that pass through a sieve with an opening of 45 μm and remain on a sieve with an opening of 20 μm is 0.02 mass% or less, The volume average particle diameter (D 50 ) of the copper powder is 30 μm or more and 90 μm or less. A brazing paste composition comprising:
2. 2. The brazing paste composition according to claim 1, wherein the copper powder contains phosphorus in an amount of 500 ppm or more and 2000 ppm or less by mass.
3. 3. The brazing paste composition according to claim 1, wherein the base metal to be brazed is stainless steel.
4. A brazing method comprising applying the brazing paste composition according to any one of claims 1 to 3 to at least a partial surface of one base material, and then brazing the one base material to the other base material in an inert gas atmosphere in a brazing furnace.
5. 5. The brazing method according to claim 4, wherein argon gas and / or helium gas is used as the inert gas.
Citation Information
Patent Citations
Copper welding paste for braze welding and preparation method thereof
CN103659053A
Method of manufacturing ceramic circuit board
JP2001148568A
Pasty composition for brazing and brazing method using the same
JP2003275895A
Stainless steel for brazing and brazing method
JP2010065278A
Brazing filler metal, and ceramic substrate employing same
WO2016013651A1